AKSESIBILITAS MENUJU FASILITAS KESEHATAN DI KABUPATEN SOLOK SELATAN - Zulfariani, Zulfariani; Purwaningsih, Endah (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to analyze the accessibility to health service locations in South Solok Regency, know the facilities and infrastructure of hospital health services in South Solok Regency. The research method used is descriptive qualitative with the sampling technique carried out by total sampling, The subject of this research is Hospital and Public Health Center. The results of the analysis of this study indicate that accessibility to health service facilities in South Solok Regency is not adequate, it can be seen from the condition of road access and community travel time to the location of health services. From the results of the analysis of health facilities, the area of ​​​​unserved settlements is more than the area of ​​​​serviced settlements in each of the existing health facilities. Settlements served by health facilities covering an area of ​​649.83 Ha with a percentage of the area served by 54.17% of settlements and settlements that are not served by health facilities covering an area of ​​788.87 hectares with the percentage of settlements not being served by 54.83%. Total population served by health facilities is 11.89 people/Km2. The area of ​​settlement services in South Solok Regency is 649.82 Ha with the percentage of settlement services in South Solok Regency 99.8%.